European guidelines on perinatal care: corticosteroids for women at risk of preterm birth - Daskalakis, George; Pergialiotis, Vasilios; Domellöf, Magnus; Ehrhardt, Harald; Di Renzo, Gian Carlo; Koç, Esin; Malamitsi-Puchner, Ariadne; Kacerovsky, Marian; Modi, Neena; Shennan, Andrew; Ayres-de-Campos, Diogo; Gliozheni, Elko; et al. (Journal of maternal-fetal & neonatal medicine, 2023)
of recommendationsCorticosteroids should be administered to women at a gestational age between 24+0 and 33+6 weeks, when preterm birth is anticipated in the next seven days, as these have been consistently shown to reduce neonatal mortality and morbidity. (Strong-quality evidence; strong recommendation). In selected cases, extension of this period up to 34+6 weeks may be considered (Expert opinion). Optimal benefits are found in infants delivered within 7 days of corticosteroid administration. Even a single-dose administration should be given to women with imminent preterm birth, as this is likely to improve neurodevelopmental outcome (Moderate-quality evidence; conditional recommendation).Either betamethasone (12 mg administered intramuscularly twice, 24-hours apart) or dexamethasone (6 mg administered intramuscularly in four doses, 12-hours apart, or 12 mg administered intramuscularly twice, 24-hours apart), may be used (Moderate-quality evidence; Strong recommendation). Administration of two "all" doses is named a "course of corticosteroids".Administration between 22+0 and 23+6 weeks should be considered when preterm birth is anticipated in the next seven days and active newborn life-support is indicated, taking into account parental wishes. Clear survival benefit has been observed in these cases, but the impact on short-term neurological and respiratory function, as well as long-term neurodevelopmental outcome is still unclear (Low/moderate-quality evidence; Weak recommendation).Administration between 34 + 0 and 34 + 6 weeks should only be offered to a few selected cases (Expert opinion). Administration between 35+0 and 36+6 weeks should be restricted to prospective randomized trials. Current evidence suggests that although corticosteroids reduce the incidence of transient tachypnea of the newborn, they do not affect the incidence of respiratory distress syndrome, and they increase neonatal hypoglycemia. Long-term safety data are lacking (Moderate quality evidence; Conditional recommendation).Administration in pregnancies beyond 37+0 weeks is not indicated, even for scheduled cesarean delivery, as current evidence does not suggest benefit and the long-term effects remain unknown (Low-quality evidence; Conditional recommendation).Administration should be given in twin pregnancies, with the same indication and doses as for singletons. However, existing evidence suggests that it should be reserved for pregnancies at high-risk of delivering within a 7-day interval (Low-quality evidence; Conditional recommendation). Maternal diabetes mellitus is not a contraindication to the use of antenatal corticosteroids (Moderate quality evidence; Strong recommendation).A single repeat course of corticosteroids can be considered in pregnancies at less than 34+0 weeks gestation, if the previous course was completed more than seven days earlier, and there is a renewed risk of imminent delivery (Low-quality evidence; Conditional recommendation).
Keywords: novorozenec; Infant, Newborn; Infant; Pregnancy; hormony kůry nadledvin; Humans; kojenec; Premature Birth; dítě; Child; Female; mladý dospělý; dospělí; lidé; perinatální péče; Perinatal Care; Adult; ženské pohlaví; těhotenství; betamethason; Betamethasone; Young Adult; Adrenal Cortex Hormones; předčasný porod; prospektivní studie; Prospective Studies